Fragmented QRS complex on a 12‐lead electrocardiogram predicts cardiovascular and all‐cause mortality in dialysis patients. Issue 1 (25th January 2022) - Li, Xinjian; Shi, Bingshuo; Chen, Xu; Duan, Junying; Liu, Xing; Zhang, Ruining; Li, Guangping
Abstract: Background: Cardiovascular disease (CVD) is the most common cause of mortality in end‐stage renal disease (ESRD) patients. Fragmented QRS complex (fQRS) has been reported as a helpful marker in evaluating various cardiovascular pathologies. We aimed to investigate the value of the fQRS complex clinical decision of ESRD patients receiving dialysis. Methods: This prospective observational study included 411 patients receiving hemodialysis (HD) or continuous ambulatory peritoneal dialysis (CAPD) between 2016‐01‐01 and 2020‐12‐31. The primary outcomes were all‐cause and cardiovascular (CV) mortality. Results: HD patients have elevated values of fQRS complex compared to CAPD patients (39.1% vs. 28.2%, P  = 0.027). Significantly, fQRS complex in the anterior/lateral leads is associated with all‐cause and CV mortality stronger than fQRS in the inferior leads ( P  = 0.008). In a multivariate Cox regression analysis, HD patients with fQRS complex had a higher incidence of all‐cause mortality (hazard ratio [HR] = 1.860; 95% confidence interval [CI]: [1.032, 3.349]; p  = 0.041) and CV mortality (HR = 2.989; 95% CI [1.357, 6.584]; p  = 0.007). For CAPD patients, fQRS complex was also associated with increased risk of all‐cause mortality (HR = 1.593; 95% CI [1.023, 2.580]; p  = 0.049) and increased risk of CV mortality (HR = 2.392; 95% CI [1.348, 4.173]; p  = 0.013). Conclusions: The presence of the fQRS complex was an independent predictor of all‐cause and CV mortality in HD and CAPD patients. We suggested a potential role of the fQRS complex in CV risk strata for dialysis patients and the choice of dialysis modality.